Position Location technique in Non-Line-of-Sight Environments for Wireless Sensor Networks - Nguyen, Hoc Thai; János, Levendovszky (Journal of Computer Science and Cybernetics, 2016)
In this paper a novel algorithm is proposed to provide a Steepest Ascent Search for localization problem in wireless sensor networks (WSNs). Based on the Received Signal Strength (RSS) from neighbor sensor nodes, a single Moving Beacon (MB) will scan on the path of steepest ascent to locate the positions of sensor nodes. This approach not only achieves a high degree of the localization accuracy in Non-Line-Of-Sight (NLOS) environments but also decreases the execution time considerably. For performance analysis, we compare the average location error and the average execution time versus the speed of the MB. The numerical results demonstrate that our algorithms can achieve the best performance if the MB moves under 12 (m/s). The numerical results also exhibit a better performance of our algorithms compared to other localization algorithms.